A novel drug–phospholipid complex loaded micelle for baohuoside I enhanced oral absorption: in vivo and in vivo evaluations. (September 2013) - Jin, Xin; Zhang, Zhen-Hai; Sun, E.; Tan, Xiao-Bin; Zhu, Fen-Xia; Jia, Xiao-Bin
Abstract : Baohuoside I is an effective anti-cancer drug currently used for a variety of cancers in vitro . Unfortunately, baohuoside I has a very poor solubility in both water and in organic solvents. Besides that, it is subject to significant efflux. This work therefore aimed at evaluating the ability of mixed micelles to solubilize baohuoside I, increase permeability and inhibit efflux of baohuoside I to promote oral absorption. A novel (TPGS–baohuoside I–phospholipid complex) mixed micelles was formed by phospholipid complex and TPGS to increase the solubility, enhance permeability, and inhibit efflux of baohuoside I. Micelle formation was confirmed by differential scanning calorimetry and transmission electron microscopy. The average diameters and efflux ratio of mixed micelles decreased as the ratio of TPGS increased with a respective increase in solubility of baohuoside I. Nevertheless, a slow release of baohuoside I from loaded micelles was noted. The results showed that at a 1:9 ratio for baohuoside I–phospholipid complex: TPGS in mixed micelles, solubility of baohuoside I increased up to 88 fold while the efflux ratio decreased by 85%. Their smaller size and higher zeta potential values indicated that mixed micelles would be easily absorbed and more stable. The relative bioavailability of the micelles (AUC0-∞ ) compared with baohuoside I (AUC0-∞ ) was 533%, demonstrating great potential for clinical application. Hence, the novel micelles formed with phospholipid complex and TPGS considerably increased drug concentration in the media and enhanced absorption.